An update on atrial fibrillation in 2014: From pathophysiology to treatment. (15th January 2016) - Ferrari, R.; Bertini, M.; Blomstrom-Lundqvist, C.; Dobrev, D.; Kirchhof, P.; Pappone, C.; Ravens, U.; Tamargo, J.; Tavazzi, L.; Vicedomini, G.G.
Abstract: Atrial fibrillation (AF) is the most frequently encountered cardiac arrhythmia. The trigger for initiation of AF is generally an enhanced vulnerability of pulmonary vein cardiomyocyte sleeves to either focal or re-entrant activity. The maintenance of AF is based on a "driver" mechanism in a vulnerable substrate. Cardiac mapping technology is providing further insight into these extremely dynamic processes. AF can lead to electrophysiological and structural remodelling, thereby promoting the condition. The management includes prevention of stroke by oral anticoagulation or left atrial appendage (LAA) occlusion, upstream therapy of concomitant conditions, and symptomatic improvement using rate control and/or rhythm control. Nonpharmacological strategies include electrical cardioversion and catheter ablation. There are substantial geographical variations in the management of AF, though European data indicate that 80% of patients receive adequate anticoagulation and 79% adequate rate control. High rates of morbidity and mortality weigh against perceived difficulties in management. Clinical research and growing experience are helping refine clinical indications and provide better technical approaches. Active research in cardiac electrophysiology is producing new antiarrhythmic agents that are reaching the experimental clinical arena, inhibiting novel ion channels. Future research should give better understanding of the underlying aetiology of AF and identification of drug targets, to help the move toward patient-specific therapy. Highlights: 80% of European AF patients receive adequate anticoagulation and/or rate control. High AF morbidity and mortality weigh against perceived management difficulties. Clinical research is refining indications and providing new technical approaches. Active research in electrophysiology is producing novel antiarrhythmic agents. Better understanding of aetiology and pathways will lead to targeted therapy.